Prevalence and factors associated with teenage pregnancy in Sierra Leone: evidence from a nationally representative Demographic and Health Survey of 2019 - Nuwabaine, Lilian; Sserwanja, Quraish; Kamara, Kassim; Musaba, Milton W. (BMC Public Health, 2023)
Globally, teenage pregnancy remains a public health concern because of the associated maternal and perinatal morbidity and mortality. To address the extensive social, political and economic effects of teenage pregnancy, there is need for current epidemiological evidence on its prevalence and associated factors, especially from low resource settings where the burden is highest.